Prevalence of malocclusion and orthodontic treatment need in a sample of 12-15-year-old kurdish schoolchildren in Ranyia district - Zana Qadir Omer; Hashem Omer Karim (Erbil Dental Journal)
Background and objectives: In recent years, much attention has been focused on measuring the severity and prevalence of malocclusion and orthodontic treatment need worldwide,in particular, the aetiological importance of genetic factors has been reduced, considering that many malocclusions recognize a post-natal origin related to habits at early stages of life and trauma.This study aimed to determine the prevalence of malocclusion and to evaluate the need for orthodontic treatment in school going children in Ranyia district in Kurdistan region of Iraq.